Improving Peritoneal Dialysis Access in Rural Communities with Telemedicine - Brauer, Alexander; Waheed, Sana (Telehealth and Medicine Today, 2019)
Increased availability of telehealth, along with patient satisfaction with the modality and financial incentives, makes peritoneal dialysis (PD) an excellent option for qualifying patients living in rural communities. Telemedicine has the potential to radically change the delivery of dialysis care by facilitating the ability of these patients to interact with their PD team via telehealth using a computer with reliable broadband Internet, which many rural clinics and hospitals now possess. Recent legal precedents make this a possibility. Therefore, it is recommended that renal providers take advantage of these favorable conditions to expand the diversity and quality of their practice.